Study the impact of short interpregnancy interval on pregnancy outcome: a case-control study - Manchanda, Sneha; Yadav, Geeta; Ahmad, Ayesha; Gupta, Uma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The inter-pregnancy interval (IPI) refers to the period between the end of one pregnancy and the beginning of the next. It is a significant factor in maternal and neonatal health outcomes. It is typically defined as “the time span between a live birth and the conception/start of the next pregnancy”. The present study was undertaken to find an impact on the association of short interpregnancy intervals with adverse perinatal outcomes. Methods: The present study was carried out as a case-control study. All pregnant females attending the department of obstetrics and gynecology, Era’s Lucknow Medical College and Hospital were enrolled in the study with short IPI versus normal IPI. Results: Shorter interpregnancy gap was significantly associated with younger maternal age (15-25 years; RR 1.92), anemia in current pregnancy (RR=1.52), PROM (RR=15.33), birth weight <2.5 kg (RR=2.22). pregnancy complications like PROM, PIH and primary PPH were recorded in 13.8%, 1.7% and 1.7% women in current pregnancy. Conclusions: Younger married women should be apprised of the need to maintain a reasonable interpregnancy gap as per national health mission guidelines in order to ensure a safe pregnancy and better pregnancy outcomes.